Memorial de formação em Licenciatura em Pedagogia: reconstruindo a Educação Infantil e os anos iniciais do Ensino Fundamental - Monteiro, Marizeth Santos (Brasil, 2024)
In this Course Completion work, this memorial aims to report my schooling throughout my life, from childhood to adulthood, contextualizing my childhood education, my elementary school, high school and higher education, and my experiences in internships. and teaching. The reports presented in this Memorial are divided into chapters, starting with the introduction contextualizing my family, followed by chapter I: My basic education, with data on the schools where I studied and the difficulties faced in studying. In chapter II: My higher education and internship experience. Followed by chapter III: Teaching activities, I end with final considerations. This achievement means a lot to me, and to my family, as my shared story shows the reality of many young people in the countryside, who are unable to continue with their studies due to economic difficulties. So “until the Lord helped me” and will continue to help me, a cycle ends, but another cycle begins, new ideals, new goals, and let‟s go.